Enhanced therapeutic efficacy for glioblastoma immunotherapy with an oncolytic herpes simplex virus armed with anti-PD-1 antibody and IL-12 - Lei Wang; Xusha Zhou; Xiaoqing Chen; Yuanyuan Liu; Yue Huang; Yuan Cheng; Peigen Ren; Jing Zhao; Grace Guoying Zhou (Molecular Therapy: Oncology)
Glioblastoma is the most common and aggressive malignant brain tumor and has limited treatment options. Hence, innovative approaches are urgently needed. Oncolytic virus therapy is emerging as a promising modality for cancer treatment due to its tumor-specific targeting and immune-stimulatory properties. In this study, we developed a new generation of oncolytic herpes simplex virus C5252 by deletion of a 15-kb internal repeat region and both copies of γ34.5 genes. Additionally, C5252 was armed with anti-programmed cell death protein 1 antibody and interleukin-12 to enhance its therapeutic efficacy for glioblastoma immune-virotherapy. In vitro and in vivo experiments demonstrate that C5252 has a remarkable safety profile and potent anti-tumor activity against glioblastoma. Mechanistic studies demonstrated that C5252 specifically induces cell apoptosis by caspase-3/7 activation via downregulating ciliary neurotrophic factor receptor α. Furthermore, the enhanced anti-tumor therapeutic efficacy of C5252 in a subcutaneous glioblastoma model and an orthotopic glioblastoma model was confirmed. Moreover, syngeneic mouse models showed that the murine surrogate of C5252 has superior anti-tumor activity compared to the unarmed backbone virus, with enhanced immune activation. Taken together, our findings support C5252 as a promising therapeutic option for glioblastoma treatment, positioning it as a highly promising candidate for clinical translation.